Beyond the Classroom Boundaries: Utilizing the School Environment to Enhance Student Engagement and Social Studies Learning Outcomes - Fatma Asneni (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Social Studies (IPS) instruction in elementary schools often suffers from theoretical monotony, leading to low student engagement and sub-standard academic outcomes. This study aims to enhance both student learning activities and academic outcomes by utilizing the school environment as a contextual learning resource for fifth-grade students at SDN 09 Marisa. Employing a Classroom Action Research (CAR) design, the study was conducted over two cycles, consisting of planning, action, observation, and reflection phases. The subjects were 17 students (6 males and 11 females). Data were collected through direct observation rubrics to measure student activity and cognitive tests to evaluate learning outcomes against the Minimum Mastery Criterion (KKM). The synthesized results demonstrated a significant improvement; initial pre-cycle data showed only a 35% classical mastery rate. Following the implementation of outdoor environmental observation in Cycle I, mastery increased to 64%, and further optimization in Cycle II resulted in an 88% mastery rate, successfully exceeding the target. Student engagement drastically shifted from passive listening to active inquiry and exploration. In conclusion, strategically utilizing the school environment as a primary learning resource effectively breaks classroom monotony, actualizes constructivist learning theories, and significantly boosts both student participation and cognitive achievement in Social Studies.